Prevalence of Persistent and Recurrent Cervical Dysplasias in Cervical Intraepithelial Neoplasia II - III Patients with Positive Margin after Loop Electrosurgical Excision Procedure (LEEP) - Eumpunthu, Tevaporn (Journal of Health Science of Thailand, 2018)
The objective of this prospective controlled clinical trial research was to study and compare the prevalence of persistent and recurrent disease in patients diagnosed as CIN II, III with positive margin by loop electrosurgical excision procedure (LEEP) between the patients with and without subsequent hysterectomy. It included 65 patients, with the diagnosis of CIN II, III with positive margin after LEEP, of department of obstetrics and gynecology, Chaoprayayomraj hospital from February 13, 2002 to March 31, 2008. The patients were divided into 2 groups. The first was a controlled group composed of 37 patients who attended follow - up examination after LEEP. The other group was experimental group composed of 28 patients who underwent hysterectomy within 6 months after LEEP. The pathology of LEEP specimens, uterus from hysterectomy and result of follow - up examination of the patients in both groups were recorded. It showed that the prevalence of persistent dysplasia was found in 24.3 percent of the controlled group and none in the experimental group which was significantly different( p=0.008). The prevalence of the recurrent dysplasia in the controlled group and the experimental group was 16.2 percent and 7.1 percent respectively which was not significantly different (p =0.449) The prevalence of persistent and recurrent diseases in the LEEP group was higher than the LEEP with subsequent hysterectomy group, but this might be wrong due to short period of follow up in the latter group. In conclusion, the treatment of the CIN II - III patients with positive margin after LEEP would be a regular follow up or performed a repeated diagnostic excisional procedure, hysterectomy was acceptable if a repeated excisional procedure was not feasible.